2021
DOI: 10.1172/jci.insight.141912
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant gorilla adenovirus HPV therapeutic vaccine PRGN-2009

Abstract: There are approximately 44,000 cases of human papillomavirus–associated (HPV-associated) cancer each year in the United States, most commonly caused by HPV types 16 and 18. Prophylactic vaccines successfully prevent healthy people from acquiring HPV infections via HPV-specific antibodies. In order to treat established HPV-associated malignancies, however, new therapies are necessary. Multiple recombinant gorilla adenovirus HPV vaccine constructs were evaluated in NSG-β2m –/– peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Human papillomavirus (HPV)-oncogenesis being associated with the constitutive expression of HPV proteins E6 and E7 in tumors, many clinical trials have investigated the efficacy of therapeutic vaccines targeting E6 and E7, but none has led to approval for clinical use so far ( 83 ). However, a novel therapeutic gorilla adenovirus HPV vaccine, PRGN-2009, has shown promise when tested in PBMC-humanized NSG mice bearing human HPV16 + cervical tumors as it reduced tumor growth and increased CD8 + and CD4 + T cell levels in the TME, supporting its use in clinical trials ( 84 ) ( Figure 2D ).…”
Section: Humanized Mouse Models In Cancer Immunotherapy Researchmentioning
confidence: 99%
“…Human papillomavirus (HPV)-oncogenesis being associated with the constitutive expression of HPV proteins E6 and E7 in tumors, many clinical trials have investigated the efficacy of therapeutic vaccines targeting E6 and E7, but none has led to approval for clinical use so far ( 83 ). However, a novel therapeutic gorilla adenovirus HPV vaccine, PRGN-2009, has shown promise when tested in PBMC-humanized NSG mice bearing human HPV16 + cervical tumors as it reduced tumor growth and increased CD8 + and CD4 + T cell levels in the TME, supporting its use in clinical trials ( 84 ) ( Figure 2D ).…”
Section: Humanized Mouse Models In Cancer Immunotherapy Researchmentioning
confidence: 99%
“…These characteristics subjected to use the non-human Ads as a vector for gene therapy and recombinant vaccine development so as to overcome the pre-existing antibodies that exists against human adenoviral vectors. There are numerous non-human adenoviral vectors that have used for recombinant vaccine development and gene therapy such as gorilla adenovirus vector (GC-46), chimpanzee adenoviral vectors (ChAdOx1 nCoV-19, ChAd1, ChAd2, ChAd3, ChAd5, ChAd6, ChAd7, and ChAd68); bovine adenoviral vectors; fowl adenoviral vectors; canine adenoviral vectors, ovine adenoviral vectors; porcine adenoviral vectors ( 36 40 ).…”
Section: General Information On Adenovirusesmentioning
confidence: 99%
“…The study revealed that PRGN-2009 treatment reduced tumor volume and increased CD8+ and CD4+ T cells in the tumor microenvironment of humanized mice bearing the human cervical tumor SiHa. The PRGN-2009 monotherapy in the syngeneic TC-1 model also reduced tumor volumes and weights, generated high levels of HPV16 E6–specific T cells, and increased multifunctional CD8+ and CD4+ T cells in the tumor microenvironment ( 40 ).…”
Section: Application Of Adenoviruses In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…HPV is a small, nonenveloped double-stranded DNA virus [ 8 ]. Among the high-risk HPV types, HPV16 and HPV18 are major viral carcinogens, accounting for the development of up to nearly 5% of the total cancer incidence worldwide [ 9 , 10 ]. HPV E6 and E7 are two major oncoproteins encoded by HPV 16 and 18 [ 11 ], which have been shown to promote tumorigenesis by inducing cell immortality and migration, changing the cell cycle, controlling apoptosis, and fostering avoidance of host immune surveillance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%